An adjuvant-modulated vaccine response in human whole blood - Jalil Hakimi; Ali Azizi; Salvador F. Ausar; Stephen M. Todryk; Nausheen Rahman; Roger H. Brookes (Taylor & Francis Group, 2017)
The restimulation of an immune memory response by in vitro culture of blood cells with a specific antigen has been used as a way to gauge immunity to vaccines for decades. In this commentary we discuss a less appreciated application to support vaccine process development. We report that human whole blood from pre-primed subjects can generate a profound adjuvant-modulated, antigen-specific response to several different vaccine formulations. The response is able to differentiate subtle changes in the quality of an immune memory response to vaccine formulations and can be used to select optimal conditions relating to a particular manufacture process step. While questions relating to closeness to in vivo vaccination remain, the approach is another big step nearer to the more relevant human response. It has special importance for new adjuvant development, complementing other preclinical in vivo and in vitro approaches to considerably de-risk progression of novel vaccines before and throughout early clinical development. Broader implications of the approach are discussed.